Manufacturing of Sugar Measurement Devices - Jabbar, Zahraa Malik; Mohammed, Hader Imad; Dawood, Manar Gthalan; Hadi, Noor Alhuda Haider (American Journal of Botany and Bioengineering, 2025)
This report describes the methods employed to fabricate a sugar measurement device that will assist the development of an automatic sugar cane harvester. A sugar measurement device is essential for a sugar cane harvester to predict the quality of the harvested sugar cane at the point of harvest. This capability would allow better management of sugar cane harvesting. For example, harvested sugar cane of different quality could be controlled separately prior to transport by different means. People currently evaluate the quality of sugar cane after the harvest at the sugar mill. This means that the quality of the harvested cane cannot be changed. This report covers the design, construction, calibration, and testing of a sugar measurement device for a sugar cane harvester. The sugar measurement device itself consists of an optical assembly and a mount. The optical assembly is the most critical component since it contains a sugar mass measurement device and is responsible for accurately calibrating sugar mass measurements. The mount is necessary for mounting the optical assembly in a sugar cane harvester. Calibration involves determining the parameters that characterize the response of a sugar mass measurement device to the measured sugar. An optical assembly for measuring the sugar mass contained within a pipe based on diffuse reflectance theory is constructed. The sensor is a fiber optic diffuse reflectance sensor with a controlled exit angle. An acquisition device is used for storing the data collected by the sensor. It also provides a mechanism to evaluate the properties of the sugar mass measurement device, to determine the calibration parameters of the measurement and to validate the device’s performance.